Model of History Education Laboratory Management - Tarunasena Tarunasena; Ayi Budi Santosa; Iing Yulianti (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The background of this research is based on the importance of forming professionalhistory teacher candidates in accordance with the above mentioned expectations,the Department of Historical Education needs to empower and develop the HistoryLaboratory as a superior program. The History Education Laboratory is centered onthe field of science, a place of authority and academic integrity. The HistoryEducation Laboratory was formed in order to meet the needs of the department andthe development of academics. The main limitation of this research problem is"what is the model of Management of Historical Education Laboratory in HigherEducation from the Organization and Administration aspects? Qualitative researchmethods are research procedures that produce descriptive data in the form ofwritten or oral words from and observable behavior. The objective of the researcherto use a qualitative approach is to look for a complex and holistic description of thesubject matter studied in this regard regarding the management model of theHistorical Education laboratory in tertiary institutions.